2015
DOI: 10.3390/nu7105433
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Docosahexaenoic Acid Feeding on Lipid Composition and Brain Fatty Acid-Binding Protein Expression in Rats

Abstract: Arachidonic (AA) and docosahexaenoic acid (DHA) brain accretion is essential for brain development. The impact of DHA-rich maternal diets on offspring brain fatty acid composition has previously been studied up to the weanling stage; however, there has been no follow-up at later stages. Here, we examine the impact of DHA-rich maternal and weaning diets on brain fatty acid composition at weaning and three weeks post-weaning. We report that DHA supplementation during lactation maintains high DHA levels in the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…In agreement with other studies [ 20 , 21 ], a predominance of palmitic acid (16:0), stearic acid (18:0), oleic acid (18:1 n -9), AA (20:4 n -6), and DHA (22:6 n -3) was described in the brains of both groups during the experimental period.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with other studies [ 20 , 21 ], a predominance of palmitic acid (16:0), stearic acid (18:0), oleic acid (18:1 n -9), AA (20:4 n -6), and DHA (22:6 n -3) was described in the brains of both groups during the experimental period.…”
Section: Discussionsupporting
confidence: 92%
“…To investigate the effects that a DHA-rich maternal diet compared with an ARA-only diet have on brain fatty acid composition of Sprague-Dawley rats, Elsherbiny et al [ 219 ] considered a control diet containing ARA (0.4 g/100 g of total fatty acid) vs. a DHA + ARA diet (0.9 g/100 of DHA and 0.4 g/100 g of ARA of total fatty acid). The results indicated that at three weeks postnatally the DHA-rich diet increased levels of DHA in the brain and decreased ARA by 12.8%.…”
Section: Animal Studies Of Ara Supplementationmentioning
confidence: 99%
“…The results indicated that at three weeks postnatally the DHA-rich diet increased levels of DHA in the brain and decreased ARA by 12.8%. The brain of a three-week-old rat is at a comparable stage as that of a human toddler at 2–3 years of age [ 219 ]. At six weeks (comparable to a 12–18 years old human), the DHA-induced decreases in ARA were reversed and disappeared when DHA was continued ( i.e.…”
Section: Animal Studies Of Ara Supplementationmentioning
confidence: 99%
“…) and FABP7 (Elsherbiny et al . ) was observed with dietary fatty acids. In addition, the impact of this dietary intervention on the BBB transport of exogenous DHA and brain levels of DHA was investigated.…”
mentioning
confidence: 82%